IMPROVING STUDENT LEARNING MOTIVATION THROUGH THE UTILIZATION OF VIDEO MEDIA IN EDUCATION STUDENTS - Syaparuddin Syaparuddin; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2020)
This research was motivated by the low learning motivation of class XI IPS.1 SMAN 6 Pinrang on Civics subjects. This can be seen from the behavior shown by students, students arriving late, not doing assignments, not paying attention to teacher explanations and being less active. Of the 36 students, only 3 students have high learning motivation. If calculated classically, the students' motivation to learn Civics subjects is 54.03%. This condition occurs as long as the PKn PBM teachers only use blackboards and worksheets. In order for student motivation to increase, teachers need to make a learning innovation. What the teacher can do is to use video as a learning medium. The acquisition of learning outcomes through the sense of sight is around 75%, through the sense of hearing about 13%, and through other senses around 12%. Formulation of the problem "Can the use of video media in Citizenship Education subjects increase student motivation in class XI.IPS.1 SMAN 6 Pinrang?". The research objective was to determine whether or not there was an increase in student motivation in Citizenship Education class XI IPS.1 SMAN 6 Pinrang through the use of video media. The benefit of this research is to provide input to increase student learning motivation through the use of video media, so that it can be used as a consideration in the use of learning media. This type of research is Classroom Action Research, with the research location at SMAN 6 Pinrang which is located at Jalan Poros Pinrang-Rappang. Research variables: input variables; student learning motivation before using video as a learning medium. Process variable: learning activities using video as a learning medium. Output variable: increasing student motivation after using video as a learning medium. The research results were obtained through two cycles, cycle I and cycle II. Pre-cycle student learning motivation is 54.03% (low) then in cycle I student learning motivation becomes 70.75% (moderate) and in cycle II increases to 75.73% (high). But at the end of the cycle there were still 2 students whose learning motivation was still low.